Indicadores de alteração hidrológica : o declínio das vazões no baixo Rio São Francisco - Vasco, Anderson Nascimento do (2015)
The evaluation of the hydrological regime constitutes a fundamental instrument for the management process in the use of water resources. The growth of water demand associated with other impacts occurred in the basin of the River São Francisco make the knowledge about the hydrologic characteristics an important instrument for the use of their water resources are optimized with less environmental impact, the analysis of changes in the lower of São Francisco river the analysis of changes in the lower of São Francisco river resulted from the successive introduction of dams along the stretches and their environmental effects are extremely important concerning the revitalization of this river. Therefore, In Chapter I, a In Chapter I, bibliographic review about the anthropic impacts and changes the system of flows in rivers is presented; a small part of Brazilian legislation on granting the right of use of water resources and some methods and questions that assist in setting instream flows. In Chapter II, In Chapter II, a characterization of the study area with emphasis on the lower of São Francisco river was performed. In Chapter III we evaluated the magnitude of changes in flow regime in the Lower of São Francisco, caused by the construction of Sobradinho and Xingó reservoirs, and also the changes in water availability. In Chapter IV the changes in flow regime after the construction of Xingó´s reservoirs were determined by relating these changes with some ecological implications. In Chapter V, are determined instream flows by different methods that may guide the effective management of water resources in such a way to promote a water management that fits human needs and protect the ecological integrity of the aquatic ecosystem. They were identified several hydrological changes in the lower part of the River São Francisco in the period after the construction of the dams, among those changes there are the decreasing in peak, medium and minimum flows, decreasing in water availability, the end of natural floods with reduction of marginal lagoons.